A Comprehensive Review on Pharmacognostical Investigation and Pharmacology of Typhonium trilobatum - Manna, Kuntal; Debnath, Bikash; Das, Manik; Marwein, Sarapynbiang (Natural Products Journal, The, 2016)
Edible plants are vital in our diet and have ethno medicinal values as well. They are an essential source of food and highly beneficial for the maintenance of health and prevention of diseases. The genus Typhonium (Family: Araceae) is a leafy vegetable and comprises of about 69 species of tuberous perennial herbs. It is widely distributed in tropical region of India, China, Bangladesh, Burma, Siam, Ceylon, Malaysia and North Australia. In India, Typhonium trilobatum is well grown in north-eastern zone on rainy season and local name is “Kharkan” and its english name is “Bengal Arum”. It contains several phytochemical and nutraceutical constituents. Literature reveals that it has multiple pharmacological activities, which include anti-inflammatory activity, analgesic activity, wound healing activity, anti-bacterial activity, anti-fungal activity, anti-diarrheal activity, larvicidal activity, anti-oxidant activity, anti-diabetic activity, and anti-depressant activity. A species of genus Typhonium; Typhonium flagelliforme was found to possess significant anticancer activity. In this review, taxonomical, micro-morphological and karyotypic description of Typhonium trilobatum along with the pharmacological activities reported in last few decades is summarized. This review would assist researchers to get pertinent information for further research about this plant.
Keywords: pharmacological activity